Zur Phototsynthese antarktischer Kryptogamen unter besonderer Berücksichtigung von Photoinhibition - Schlensog, Mark (Christian-Albrechts-Universität zu Kiel, 2000)
In polar regions high quantum flux densities occur regularly during springtime and summer due to the high albedo of the persisting snowcover. Strong irradiances in the visible wavelength band are known to induce photoinhibition of photosynthesis. This factor could, therefore, be relevant for the primary productivity of mosses and lichens dominating the antarctic vegetation. Under controlled conditions in the laboratory a wide range of investigated species showed a reduced efficiency of photosystem II following an exposure to high quantum flux densities of 1500 µmol m-2 s-1. In mosses from shaded habitats like Pohlia cruda a treatment of two hours with strong light led to a reduction of gross photosynthesis and electron transport rate through photosystem II of 52%, that was not reversible within days. In the lichens Usnea aurantiaco-atra and Umbilicaria antarctica from dry, open exposed fellfield habitats even stronger effects were found. However, in the field these species experienced strong irradiance almost in the desiccated and highly resistant state only. Mosses as Sanionia uncinata, which dominate habitats with a constant water supply, did not desiccate in the field. Regularly occurring reductions of photosystem II efficiency in the field were quickly reversible. They seem to be part of protection mechanisms as the xanthophyll cycle that enable the organisms to perform photosynthesis at fluctuating light. The photosynthetic performance of all investigated organisms seems, therefore, to be well adapted to the light and temperature conditions in the antarctic summer.